Axes of education functional inspection Andalucia. Brief analysis of some actions and challenges for development - José Francisco Pérez Aguilar (ADIDE Federación, 2014)
The Spanish Constitution places the responsibility for the inspection of the education system to the government. This mandate is achieved through the organic laws of education, attributing it to the education authorities that have made the inspection functions. In Andalusia, the concrete and singular answer to the above is the framework that develops competence committed around three functional axes. This framework composes the actions that each educational inspection is empowered to conduct in the exercise of their functions. Currently , the framework is completed with the functional axes of preferred intervention and intervention model in order to unite and harmonize all activities that are designed and developed under the General Plan of Action for the Education Inspectorate . However, their development poses a number of opportunities for improvement that could become this century's challenges.